Old-Age Employment and Hours of Work Trends: Empirical Analysis for Four European Countries - Arjeta Aliaj; Xavier Flawinne; Alain Jousten; Sergio Perelman; Lin Shi (Institute for the Study of Labor (IZA), 2016)
For the last two decades, the increase of employment among cohorts of individuals aged 50+ has been a policy objective on the European employment agenda. The present paper takes stock of the situation as observed in Belgium over the time period 1997-2011. First, we provide analysis on the evolution of older workers' employment in Belgium and its neighboring countries Germany, France and the Netherlands using the EU Labour Force Survey. Second, we characterize the different employment and hours of work patterns for different age sub-groups (50-54, 55-59, 60-64) and provide evidence on their respective evolution. The results show that employment rates among older workers started to catch-up with employment rates of younger cohorts as of 2001, and with more acuity after 2006. This effect dominates the observed negative effect on hours of work and hence leads to an increase in total hours of work of the cohort – net of any purely demographic effects.
Keywords: J08; J21; J26; 330; retirement; employment; hours of work